Given that Trade Wars Tend to Be More Regular Between the World’s Economic Powers, Does Free Trade Still Make Sense Today? — Through the Analysis of Sino-American Relations and Some Cases - Ming Pan (Law and Economy, 2023)
Since World War II, as the need to restore economic production in various countries continues to increase, advocating trade liberalization seems to be a global trend. In recent years, however, some countries’ efforts to protect their trade seem to be bucking this trend. How free should Free trade be? How much should each country concede? Are the effects of the trade war purely bad? Or are there some benefits? How should we deal with these situations in the future? These are the questions discussed in this article. The attitude of individual countries towards the trade war and trade liberalization is undoubtedly the key. Does it pay to be a gentleman in today’s world of international trade? After all, trade has a profound impact on politics and many other areas.